2000
DOI: 10.1090/s0002-9947-00-02412-0
|View full text |Cite
|
Sign up to set email alerts
|

Power operations in elliptic cohomology and representations of loop groups

Abstract: Abstract. Part I of this paper describes power operations in elliptic cohomology in terms of isogenies of the underlying elliptic curve. Part II discusses a relationship between equivariant elliptic cohomology and representations of loop groups. Part III investigates the representation of theoretic considerations which give rise to the power operations discussed in Part I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…In discussing the motivation for Proposition 17, we used the cohomology theory K[[q]][q −1 ] and Adams operations. However, it would be nice to phrase these ideas is in terms of the power operations in elliptic cohomology considered by Ando [1]. We also refer the reader to [18] for more background and further considerations.…”
Section: Now We Havementioning
confidence: 99%
See 1 more Smart Citation
“…In discussing the motivation for Proposition 17, we used the cohomology theory K[[q]][q −1 ] and Adams operations. However, it would be nice to phrase these ideas is in terms of the power operations in elliptic cohomology considered by Ando [1]. We also refer the reader to [18] for more background and further considerations.…”
Section: Now We Havementioning
confidence: 99%
“…This might suggest K [[q]][q −1 ] as the first candidate for elliptic cohomology. This approach was indeed pursued by Ando [1], and leads to some valuable conclusions; in particular, K [[q]][q −1 ] is the "homotopical counterpart" of the Tate curve. However, we want to go further: the coefficient ring of the Tate curve does not consist of modular forms of any kind, so this approach does not explain the modularity of the Thompson series.…”
Section: Introductionmentioning
confidence: 99%
“…In a sense, the paper at hand is a following to Ando's [And00] and [And03], taking apart the ideas presented in those papers and rearranging them into a new picture. The most important new feature is that our derivation of the Weyl-Kac formula as a push-forward is entirely a compactmanifold argument.…”
Section: The Elliptic Weyl Character Formulamentioning
confidence: 99%
“…Let G be a simple and simply connected compact Lie group with weight lattice Λ and Weyl group W . In [Loo77], Looijenga considers two graded rings (see also [And00]).…”
Section: The Ring T H W *mentioning
confidence: 99%
“…where W (F p n ) is the ring of Witt vectors with coefficients in the finite field F p n with p n elements. Power operations in Morava E-theory were first studied by Ando in [1,2], where he used power operations in complex cobordism to produce power operations in Morava E-theory. In [6] Goerss-Hopkins showed that Morava E-theory supports an E ∞ -ring spectrum structure unique up to homotopy, which implies the existence of an H ∞ -ring spectrum structure on Morava E-theory.…”
Section: Introductionmentioning
confidence: 99%